Propiedades magneto-estructurales de los compuestos CeCO_1-xFe_xSi Y CeTi_1-xSc_xGe. - Carreras Oropesa, William G. (Comisión Nacional de Energía Atómica. Instituto Balseiro, 2018)
Fil. Carreras Oropesa, William G.. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina